Analysis on an optimal transmittance of Fresnel lens as solar concentrator. (1st September 2020) - Ma, Xinglong; Jin, Rihui; Liang, Shen; Liu, Shuli; Zheng, Hongfei
Highlights: The ideal-shape differential equation of Fresnel lens has been derived out. A Fresnel lens was designed by considering the ideal shape and the manufacturing. The problem of the focal length's change of Fresnel lens was well coped. The Fresnel solar concentrator can provide heat of 170℃ with efficiency of 0.48. Abstract: This paper presents a novel method approaches to simplify refractions on prisms to get the ideal shape of the Fresnel lens. A simplification is about to use one refraction on the upper surface to replace the two refractions on the upper and the lower surfaces. A differential equation that describes the ideal shape of Fresnel lens has been derived out. It shows that the particular solution of the differential equation is a bunch of confocal curves. Especially, the ideal curves are closing to their basic circle when total refracted angle less is than 30°, which makes it reasonable to use the basic circle as the profile of Fresnel lens. Then a Fresnel lens was designed with considering material and manufacturing technology. Then an analysis on the focal length change during the tilt incidence was mainly carried via simulation and experiment. It is found that the effective tilt incident angle can be enhanced from 7° to 32° by lifting up the position of the receiver and adding a simple mirror secondary reflector. The experimental result shows that the Fresnel solar concentrator is working efficiently during the time from about 10:00 to 14:30 a day. The steady output temperatures are 125 °C, 150 °C and 170 °C, with collection efficiencies are about 0.53, 0.48 and 0.44. It can well satisfy mid-temperature solar thermal application.